Remote Assessment of Platelet Function in Patients with Acute Stroke or Transient Ischaemic Attack. (24th May 2017) - Bath, Philip M.; May, Jane; Flaherty, Katie; Woodhouse, Lisa J.; Dovlatova, Natalia; Fox, Sue C.; England, Timothy J.; Krishnan, Kailash; Robinson, Thompson G.; Sprigg, Nikola; Heptinstall, Stan; Investigators, TARDIS
Abstract : Background . The TARDIS trial assessed the safety and efficacy of intensive versus guideline antiplatelet agents given for one month in patients with acute stroke or TIA. The aim of this substudy was to assess the effect of antiplatelet agents taken at baseline on platelet function reactivity and activation. Methods . Platelet function, assessed by remotely measured surface expression of P-selectin, was assessed in patients at their time of randomisation. Data are median fluorescence values. Results . The aspirin P-selectin test demonstrated that platelet expression was lower in 494 patients taking aspirin than in 162 patients not: mean 210 (SD 188) versus 570 (435), difference 360.3 (95% CI 312.2–408.4) (2 p < 0.001 ). Aspirin did not suppress P-selectin levels below 500 units in 23 (4.7%) patients. The clopidogrel test showed that platelet reactivity was lower in 97 patients taking clopidogrel than in 585 patients not: 655 (296) versus 969 (315), difference 314.5 (95% CI 247.3–381.7) (2 p < 0.001 ). Clopidogrel did not suppress P-selectin level below 860 units in 24 (24.7%) patients. Conclusions . Aspirin and clopidogrel suppress stimulated platelet P-selectin, although one-quarter of patients on clopidogrel have high on-treatment platelet reactivity. Platelet function testing may be performed remotely in the context of a large multicentre trial. Trial registrationISRCTN47823388 .